2017
DOI: 10.3389/fnmol.2017.00410
|View full text |Cite
|
Sign up to set email alerts
|

HIV Alters Gap Junction-Mediated Intercellular Communication in Human Brain Pericytes

Abstract: Despite successful control of viremia by combined antiretroviral therapy, brain infection and its resulting neurocognitive impairment remain a prevalent comorbidity in HIV infected individuals. HIV invades the brain early in the course of infection via penetration through the blood-brain barrier (BBB). While the impact of HIV on BBB astrocytes and endothelial cells is relatively well studied, the role of pericytes in BBB regulation during HIV infection remains unclear; however, it is known that a selective pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 76 publications
(103 reference statements)
3
39
0
2
Order By: Relevance
“…CXCR4 and CXCR5 contribute to HIV-induced CNS impairment when the BBB is compromised, which is associated with increased microvascular permeability. 84 Thus, gap junctions in pericytes mediate HIV-induced loss of BBB integrity. Additionally, although HIV infects only a small fraction of pericytes, the damage that it inflicts is amplified by gap junctions that spread viral factors to adjacent uninfected cells (Fig 2).…”
Section: Human Immunodeficiency Virus (Hiv) and Gap Junctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR4 and CXCR5 contribute to HIV-induced CNS impairment when the BBB is compromised, which is associated with increased microvascular permeability. 84 Thus, gap junctions in pericytes mediate HIV-induced loss of BBB integrity. Additionally, although HIV infects only a small fraction of pericytes, the damage that it inflicts is amplified by gap junctions that spread viral factors to adjacent uninfected cells (Fig 2).…”
Section: Human Immunodeficiency Virus (Hiv) and Gap Junctionsmentioning
confidence: 99%
“…Pericytes in the human brain express C‐X‐C chemokine receptor type (CXCR)4 and CCR5, which are the two major co‐receptors participating in the HIV‐1 infection process. CXCR4 and CXCR5 contribute to HIV‐induced CNS impairment when the BBB is compromised, which is associated with increased microvascular permeability . Thus, gap junctions in pericytes mediate HIV‐induced loss of BBB integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from it, it was also shown that HIV infection may also be propagated from the infected pericytes of the blood-brain barrier to other cells through gap junction/hemichannels-mediated intercellular communication. It has been demonstrated that HIV infection increased the expression of connexin 43 on the brain pericytes and inhibition of gap junctions by carbenoxolone was shown to prevent spreading of HIV infection within the brain [76].…”
Section: Deleterious Effects Of Connexins In Hiv-induced Dementiamentioning
confidence: 99%
“…Pericytes have a crucial role in the formation and maintenance of the Blood Brain Barrier (BBB) integrity, and are also important mediators of neuroinflammation (Cho et al , 2017; Jansson et al , 2014; Rustenhoven et al , 2017). Their significance to BBB function is also highlighted by increased density of pericytes covering the central nervous system (CNS) vasculature, when compared to capillaries and venules in other parts of the body (Aguilera and Brekken, 2014; Armulik et al , 2010; Bell et al , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The major cells in the CNS supporting HIV-1 replication are microglia and macrophages, but the virus also has an ability to infect pericytes and astrocytes, and although at a low level, their infection was found to disrupt the integrity of the endothelial barrier (Cho et al , 2017; Churchill et al , 2006; Eugenin et al , 2011; Nakagawa et al , 2012; Thompson et al , 2011; Tornatore et al , 1994; Wiley et al , 1986). Permissiveness of pericytes to non-productive HIV-1 infection suggests that the cells might support viral latency.…”
Section: Introductionmentioning
confidence: 99%